2013
DOI: 10.1007/s00405-013-2557-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuromonitoring in thyroidectomy: a meta-analysis of effectiveness from randomized controlled trials

Abstract: Neuromonitoring in thyroid surgery has been employed to make nerve identification easier and decrease the rates of laryngeal nerve injuries. Several individual randomized controlled trials (RCTs) have been published, which did not identify statistical differences in the rates of recurrent laryngeal nerve (RLN) or external branch of the superior laryngeal nerve (EBSLN) injuries. The objective of this report is to perform meta-analysis of the combined results of individual studies to measure the frequency of RLN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
102
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(111 citation statements)
references
References 43 publications
5
102
1
3
Order By: Relevance
“…Similarly, a retrospective study on 308 patients found a lower upper aerodigestive (UADS) score, indicating fewer symptoms, in patients who had undergone thyroidectomy with IONM than those who had not [18]. Likewise, a meta-analysis of available randomised studies found a lower frequency of temporary EBSLN damage with use of IONM, and a nonsignificant tendency towards a lower rate of permanent EBSLN damage [10]. In this survey, endocrine surgeons reported a much lower frequency of pre-and postoperative laryngoscopy and voice recording, than H&N surgeons.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Similarly, a retrospective study on 308 patients found a lower upper aerodigestive (UADS) score, indicating fewer symptoms, in patients who had undergone thyroidectomy with IONM than those who had not [18]. Likewise, a meta-analysis of available randomised studies found a lower frequency of temporary EBSLN damage with use of IONM, and a nonsignificant tendency towards a lower rate of permanent EBSLN damage [10]. In this survey, endocrine surgeons reported a much lower frequency of pre-and postoperative laryngoscopy and voice recording, than H&N surgeons.…”
Section: Discussionmentioning
confidence: 92%
“…However, identification can be facilitated by using intraoperative neural monitoring (IONM) [8,9]. Furthermore, IONM significantly lowered the risk of temporary EBSLN paresis, and there was a non-significant trend toward a lower risk of permanent EBSLN damage with IONM in a recent meta-analysis [10].…”
Section: Introductionmentioning
confidence: 98%
“…The data from the recent meta-analysis showed that the frequency of RLN injury was 1% in the neuromonitor group and 1.6% for the standard group, which was a no significant difference (6).…”
Section: Effectiveness Analysismentioning
confidence: 97%
“…The probabilities of RLN injury were obtained from a previous meta-analysis (6). For loss of signal probability, we used information from a study by Sitges-Serra, et al (9) (table 1).…”
Section: Probabilitiesmentioning
confidence: 99%
See 1 more Smart Citation